PENGARUH INKLUSI KEUANGAN DAN LITERASI KEUANGAN TERHADAP KINERJA USAHA UMKM: STUDI EMPIRIS DI KABUPATEN LAMPUNG SELATAN - Nofitasari, Susi; Alfina, Alfina (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in encouraging regional economic growth, including in South Lampung Regency. However, limited access to formal financial services and low levels of financial literacy are still the main obstacles affecting the performance of MSME businesses. This study aims to analyze the influence of financial inclusion and financial literacy on the business performance of MSMEs in South Lampung Regency. This study uses a quantitative approach with a survey method. Primary data was obtained through the distribution of questionnaires to MSME actors who were used as research respondents. The data analysis technique used is multiple linear regression analysis (or SEM-PLS, adjustable) to test the influence of financial inclusion and financial literacy variables on MSME business performance. The results of the study show that financial inclusion and financial literacy have a positive and significant effect on the performance of MSME businesses. The findings of this study are expected to be the basis for local governments, financial institutions, and related stakeholders in formulating policies and programs for empowering MSMEs that are oriented towards increasing access to and understanding of finance to encourage the sustainability and competitiveness of MSMEs in South Lampung Regency.